The Association of Mechanism of Injury with Predictable Injury Patterns: A Systematic Review - Marcella Jesslyn; Ryandi Satrio (The International Journal of Medical Science and Health Research, 2025)
INTRODUCTION: The mechanism of injury (MOI) is a cornerstone of trauma assessment, founded on the principle that the transfer of kinetic energy to the body produces specific and predictable patterns of tissue damage. An understanding of these patterns is critical for effective prehospital triage, rapid in-hospital diagnosis, and anticipatory patient management. This systematic review aims to synthesize the existing evidence linking specific blunt and penetrating trauma mechanisms to their resultant injury constellations across diverse patient populations. METHODS: A systematic search of PubMed, Google Scholar, Semanthic Scholar, Springer was conducted for original research published between January 2000 and December 2024. Studies were included if they quantitatively evaluated the association between a defined MOI and specific injury patterns in human subjects. Data on study design, population, MOI, and outcomes were extracted. The quality of included studies was assessed using the Cochrane Risk of Bias tool for non-randomized studies. A qualitative synthesis of the findings was performed, categorizing results by MOI and patient demographic. RESULTS: A total of 18 studies met the inclusion criteria, encompassing a range of blunt and penetrating trauma mechanisms. Consistent and strong associations were identified. In blunt trauma, fall direction in the elderly was highly predictive of fracture location: sideways falls with hip fractures (Odds Ratio 3.68), forward falls with forearm/patella fractures, and backward falls with spinal fractures. High-energy falls from height were associated with a predictable pattern of axial loading injuries, including calcaneal, pelvic, and spinal fractures. Motor vehicle collisions (MVCs) demonstrated distinct patterns based on impact vector; side impacts were associated with a higher incidence of thoracic, pelvic, and proximal upper extremity injuries compared to frontal impacts. In pediatric MVCs, age-dependent patterns were observed, with severe head injuries predominating in young children (0-8 years) and abdominal injuries in adolescents (9-17 years). Penetrating trauma from gunshot wounds was associated with high mortality, particularly with cranial involvement (41% mortality), and a high degree of occult internal injury. DISCUSSION: The evidence robustly supports the hypothesis that MOI is a powerful predictor of injury patterns, grounded in fundamental biomechanical principles. However, the predictive utility of MOI is significantly modulated by patient-specific factors, most notably age and physiological reserve. In geriatric patients, low-energy mechanisms frequently produce injury patterns characteristic of high-energy trauma in younger adults. The clinical value of MOI lies not only in field triage but also as a cognitive tool to guide diagnostic strategy and maintain a high index of suspicion for occult injuries, particularly in patients who appear physiologically stable upon initial presentation. CONCLUSION: A strong, evidence-based association exists between the mechanism of injury and predictable patterns of injury. This knowledge is essential for optimizing trauma care, from prehospital triage to definitive management. Future research should focus on developing more sophisticated predictive models that integrate MOI with patient-level factors such as frailty to enhance triage accuracy and improve patient outcomes.